PENGELOLAAN OBJEK WISATA DANAU BANDAR KAYANGAN OLEH DINAS KEBUDAYAAN DAN PARIWISATA KOTA PEKANBARU TAHUN 2017 - Ashari, Nazar; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Bandar Kayangan lake is one of tourist attraction in Pekanbaru. The place is strategic, it’s not far away from center city of Pekanbaru and has facilities and infrastructure quite complete for a tourist attraction. Culture and tourism departement as direct manager Bandar Kayangan lake it seems can’t maximizing potentials Bandar Kayangan lake. Therefore researcher want to see how the management of Bandar Kayangan lake by by culture and tourism departement and obstacles that faced by culture and tourism departement in manage Bandar Kayangan lake.The purposes of this research are first, to know how the management of Bandar Kayangan Lake tourist attraction by culture and tourism departement Pekanbaru in 2017. Second, to know what the obstacles that faced by culture and tourism departement in manage Bandar Kayangan lake in 2017. The method of this research is qualitatif. Technic of data collection is indepth interview and documentation. While data analize did by describe the data that got,then analized with explanations so it can answer research formula.`the result of this research to show manage Bandar Kayangan lake, culture and tourism departement can’t maximizing it, seem from the plans can’t do them,and control is weak,it caused by regulations that adjust tourist attraction specially Bandar Kayangan lake are nothing, limititation of budget on manage Bandar Kayangan lake and limitations of human resources especially Technical Service Unit Depatment Bandar Kayangan lake that direct manage Bandar Kayangan lake.Keywords: Management, Government Management, Bandar Kayangan Lake